Keseimbangan Kerja-Hidup Sebagai Pemediasi Peran Penting Dukungan Supervisor dalam Mempertahankan Karyawan : - - Andarwulan Widyastuti , Nuke Dewi; Susanti, Riana; Amir, Ja'far (Innovative: Journal Of Social Science Research, 2025)
In the last decade, the work-life balance has become the main focus of millennial workers and Generation Z. The phenomenon of quiet quit is also a management problem. The amount of money that must be incurred for the employee replacement process has made this research on job retention urgent and important. The SEM-PLS approach was used to analyze a questionnaire distributed to 122 employees in the timber industry. It is a valuable finding that supervisor support and work-life balance significantly effect to the job retention. VAF value 12,6 % only in mediating role of work-life balance in relation between supervisor support to the job retention or no Mediation role. It recomendad that the company shout enhance role for optimize supervisor function in create balances between work and life of employee